Opening the 'Vaccine Hesitancy' black box: how trust in institutions affects French GPs' vaccination practices. (2nd July 2016) - Raude, Jocelyn; Fressard, Lisa; Gautier, Arnaud; Pulcini, Céline; Peretti-Watel, Patrick; Verger, Pierre
ABSTRACT: Background : In recent years, vaccine hesitancy among health professionals has emerged as an important issue on public health agendas. However, we do not yet know very much about whether, and if so how, trust in institutions affects their practices. Methods : A path analysis model explaining the influence of trust on GPs' vaccine hesitancy was applied to a cross-sectional survey of 1, 582 French GPs performed in 2014. We hypothesized that distrust in public health institutions influences GPs' concerns about the safety of various vaccines, their perceptions about the importance of vaccination, their self-efficacy in the doctor-patient relationship, and ultimately their vaccination recommendations to patients. Results : GPs' trust in institutions was found to be significantly associated with lower vaccine hesitancy, an association mediated to a large extent by the vaccine's perceived safety (β = 0.09, P  < 0.01) and the importance of vaccination (β = 0.46, P  < 0.001). Conclusion : These results suggest that restoration of high vaccination coverage may require the re-establishment of a significant degree of trust in the public health system among health professionals.